An Msh3 ATPase domain mutation has no effect on MMR function. (December 2017) - Edwards, Yasmin
Abstract Objective To demonstrate that the Msh3 ATPase domain is required for DNA mismatch repair and tumor suppression in a murine model. Results The DNA mismatch repair proteins are members of the ABC family of ATPases. ATP binding and hydrolysis regulates their mismatch repair function. In the current study, a mouse model was generated harboring a glycine to aspartic acid residue change in the Walker A motif of the ATPase domain of Msh3. Impaired ATP mediated release of theMsh2 -Msh3 GD/GD complex from it's DNA substrate in vitro confirmed the presence of an ATPase defect. However, the mismatch repair function of the protein was not significantly affected. Therefore, mutation of a critical residue within the ATPase domain of Msh3 did not preclude mismatch repair at the genomic sequences tested. Indicating that Msh3 mediated mismatch function is retained the absence of a functional ATPase domain.